2014
DOI: 10.1007/s11255-014-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of end-stage renal disease and Alzheimer’s disease in the elderly through a comprehensive geriatric assessment

Abstract: The management of geriatric HD patients is substantially complex. Depression, cognitive impairment and decrease in functional capacity can often be overlooked, so findings may be ascribed to underlying kidney impairment. Therefore, comprehensive geriatric assessment should be regularly performed in HD patients in order to detect problems at an early stage, to take necessary preventative measures, to initiate treatment as soon as possible and to enhance quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…A significantly higher percentage of HD patients had a Lawton score 6 in comparison to primary care patients and similar Lawton scores were recorded in other studies. 14,39 This is in accordance with the finding that 9.4% of our HD patients used a walking device but none of the primary care patients. In addition, ''The Timed Up and Go test'' showed that 24.5% of HD patients needed more than 20 s to perform this test in contrast to 13% of elderly patients treated in primary health care (p50.0001).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A significantly higher percentage of HD patients had a Lawton score 6 in comparison to primary care patients and similar Lawton scores were recorded in other studies. 14,39 This is in accordance with the finding that 9.4% of our HD patients used a walking device but none of the primary care patients. In addition, ''The Timed Up and Go test'' showed that 24.5% of HD patients needed more than 20 s to perform this test in contrast to 13% of elderly patients treated in primary health care (p50.0001).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies either applied CGA only in HD patients 9 or compared HD patients with patients suffering from some other disease (cancer, Alzheimer) who were more severely ill than the dialysis patients. 13,14 Despite these shortcomings, our study confirmed the view highlighted in a several other studies on the feasibility and significance of CGA in HD patients. As CGA encompasses not only medical issues but all aspects of a patient's care, it enables both professionals and caregivers to identify problems that would not be revealed by standard assessment of HD, which is primarily directed to ESRDassociated disorders and quality of HD treatment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There were 46 studies meeting the inclusion criteria for final analysis [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. An overview of the reviewed articles is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%